Inter-Regional Cooperation for Sustainable Mangrove Management in Jakarta Bay - R. Budiono Subambang; Ario Damar; Taryono; Rahmat Kurnia; Dietriech G. Bengen (Jurnal Bina Praja, 2024)
An integrated institutional approach is expected to be a solution to overcome this policy fragmentation. With integrated mangrove management across jurisdictions, it can be clearer to maintain the sustainability of the mangrove ecosystem while supporting sustainable development in the coastal area of Jakarta Bay. This study aims to develop an ideal inter-jurisdictional institutional framework for mangrove management in Jakarta Bay. The study used primary and secondary data. Data analysis uses stakeholder analysis, multidimensional scaling (MDS), and interpretive structural modeling (ISM). The results of the stakeholder classification showed that local communities occupy the subject category, the key players are the central government and regional governments, universities and NGOs occupy the context setter position, and the crowded category is the private sector. The results of the MDS analysis using RAP Mangrove show a sustainability index value for the institutional dimension of 11.59%. The institutional design of the three elements, which are divided into 11 sub-elements, shows that the availability of adequate data and planning for the implementation of mangrove rehabilitation, restoring mangrove ecosystems in damaged conditions, improving the quality of degraded mangrove cover and ponds, and mangrove rehabilitation at the multi-strata government policy and program level (multi-related sectors, regional government, and village government) are the basis for the achievement of the other sub-elements. Synchronization of regulations and policies across sectors, as well as active participation from various stakeholders, are the keys to success in maintaining the sustainability of mangrove ecosystems.